Desde la educación para la salud : hacia la pedagogía de la educación alimentaria y nutricional (2006)
ABSTRACT: To identify the pedagogical referents of education interventions in health. Design: it is a qualitative, documentary research. Methods: Krippendrof’s content analysis, and Van Dijk´s discourse analysis were aplied on 45 educational experiences in health and nutrition, that have been published in scientific journals. Results: The majority of the experiences don’t have explicit pedagogical referents,only few does, but they present incoherencies in developing educational strategies that coincide with different models or theories beside the ones that they pretend propose. Among the explicit ones, there are mainly participative – active – learning oriented pedagogies, and only few have critical approach, but the implicit referents belong to traditional, classic or technicist pedagogy types. Conclusions: The coexistence between critical pedagogies in health – based on contextual and psychosocial cognitive learning models, and the traditionalists which are based on behavioral models, bring out the necessity to validate closely related theories with the current context, and to propose new theories that could lead with pedagogical postulates of the current learning models to get more efficiency in health.